Identification and Analysis of the Role of Superoxide Dismutases Isoforms in the Pathogenesis of Paracoccidioides spp. - Diana Tamayo; José F Muñoz; Ángela Lopez; Martha Urán; Juan Herrera; Clayton L Borges; Ángela Restrepo; Celia M Soares; Carlos P Taborda; Agostinho J Almeida; Juan G McEwen; Orville Hernández (Public Library of Science (PLoS), 2016)
The ability of Paracoccidioides to defend itself against reactive oxygen species (ROS) produced by host effector cells is a prerequisite to survive. To counteract these radicals, Paracoccidioides expresses, among different antioxidant enzymes, superoxide dismutases (SODs). In this study, we identified six SODs isoforms encoded by the Paracoccidioides genome. We determined gene expression levels of representative isolates of the phylogenetic lineages of Paracoccidioides spp. (S1, PS2, PS3 and Pb01-like) using quantitative RT-PCR. Assays were carried out to analyze SOD gene expression of yeast cells, mycelia cells, the mycelia-to-yeast transition and the yeast-to-mycelia germination, as well as under treatment with oxidative agents and during interaction with phagocytic cells. We observed an increased expression of PbSOD1 and PbSOD3 during the transition process, exposure to oxidative agents and interaction with phagocytic cells, suggesting that these proteins could assist in combating the superoxide radicals generated during the host-pathogen interaction. Using PbSOD1 and PbSOD3 knockdown strains we showed these genes are involved in the response of the fungus against host effector cells, particularly the oxidative stress response, and in a mouse model of infection. Protein sequence analysis together with functional analysis of knockdown strains seem to suggest that PbSOD3 expression is linked with a pronounced extracellular activity while PbSOD1 seems more related to intracellular requirements of the fungus. Altogether, our data suggests that P. brasiliensis actively responds to the radicals generated endogenously during metabolism and counteracts the oxidative burst of immune cells by inducing the expression of SOD isoforms.